The Impact of Mass Migration on the Israeli Labor Market - Friedberg, R. M. (Quarterly Journal of Economics, 2001)
Immigration increased Israel's population by 12 percent between 1990 and 1994, after emigration restrictions were lifted in an unstable Soviet Union. Following the influx, occupations that employed more immigrants had substantially lower native wage growth and slightly lower native employment growth than others. However, because the immigrants' postmigration occupational distribution was influenced by relative labor market conditions across occupations in Israel, Ordinary Least Squares estimates of the immigrants' impact on those conditions are biased. Instrumental Variables estimation, exploiting information on the immigrants' former occupations abroad, suggests no adverse impact of immigration on native outcomes.